The Effect Of Tofu Drain Flour Substitution On Cooking Loss And Sensory Quality Of Onion Cake - Raudina Ayuning Rinjani; Mariani Mariani; Nur Riska (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to analyze the effect of tofu dregs flour substitution on cooking loss and sensory quality of onion cake. This study was conducted at the Culinary Arts Education Study Program, Faculty of Engineering, Jakarta State University. The study period began from September 2024 to December 2025. This study used an experimental method with onion cake samples substituting tofu dregs flour at percentages of 20%, 30%, and 40%. Sensory quality testing in this study was conducted on 45 semi-trained panelists who assessed all product sensory quality attributes. Based on the results of the statistical hypothesis test of sensory quality using the Kruskal-Wallis test, it showed that there was no effect of onion cake substitution of tofu dregs flour at percentages of 20%, 30%, and 40% on the sensory quality aspects of color, tofu dregs aroma, tofu dregs taste, savory taste, and texture. Based on the results of the statistical hypothesis test of the cooking loss test using the ANOVA test, it showed that there was no effect on onion cake substitution of tofu dregs flour at percentages of 20%, 30%, and 40%. The conclusion of this study is to recommend onion cakes made from 30% tofu dregs flour as a substitute for tofu dregs flour to be further developed as a product that has sales value and efforts to use tofu dregs flour as a local food ingredient.